Local Wisdom of The Nurul Huda Pajagalan Islamic Boarding School as Strengthening Moral Values and Character Education For Students of STAI Al Musdariyah Cimahi - lia apriliani, Ai; Nurlatifah, Irma (UIN Sunan Gunung Djati Bandung, 2024)
Educational institutions and Islamic boarding schools are closely related, especially in developing local wisdom to create good moral values and student character. This writing is entitled